Microwave ablation versus resection for hepatocellular carcinoma within the Milan criteria: a propensity-score analysis. (September 2019) - Liu, Wenwu; Zou, Ruhai; Wang, Chenwei; Qiu, Jiliang; Shen, Jingxian; Liao, Yadi; Yang, Zhiwen; Zhang, Yuanping; Wang, Yongjin; Yuan, Yichuan; Li, Kai; Zuo, Dinglan; et al.
Background: Whether the efficient heat-generating mechanism of microwave ablation (MWA) is comparable with resection (RES) in treating hepatocellular carcinoma (HCC) remains unclear. Methods: This retrospective cohort study comprised 126 and 1183 patients with HCC meeting the Milan criteria who received MWA or RES between 2002 and 2017. We compared 5-year overall survival (OS) and recurrence-free survival (RFS) using both propensity-score matching (PSM) and inverse-probability-of-treatment-weighting (IPW) analysis and investigated the prognostic factors with multivariate Cox analysis. Results: After PSM (1:2), although MWA ( n  = 116) offered decreased 5-year RFS (30.6% versus 57.5%, p  < 0.001) compared with RES ( n  = 212), both treatments provided similar 5-year OS (82.2% versus 80.5%, p  = 0.360) because most patients with intrahepatic recurrence remained eligible for repeat treatments; similar results were found in the IPW analysis. Additionally, the comparable efficacy of MWA and RES was consistent across all subgroups: those with solitary HCC ⩽ 3.0 cm or >3.0 cm, or multifocal HCCs within the Milan criteria, patients with liver function of albumin–bilirubin grade 1 or 2, and older (⩾60 years) or younger (<60 years) patients. Multivariate Cox analysis confirmed that no difference was seen between MWA and RES in OS (hazard ratio = 0.85; p  = 0.581) in the overall population; similar results were obtained in the propensity-score-matched and IPW cohorts. Conclusions: Compared with RES, MWA offered worse RFS for HCC within the Milan criteria; however, both treatments provided equivalent long-term OS because most patients with intrahepatic recurrence remained eligible for repeat treatments.